Sulfonated polystyrene foam waste as an efficient catalyst for Friedel-Crafts type reactions - Behrang Moazzen; Roya Kamrouz; Alireza Khorshidi (Scientific Reports)
Abstract The catalytic efficiency of sulfonated polystyrene foam waste (SPS) and sulfonated gamma alumina (SGA) in Friedel-Crafts type reactions was compared. All of the materials were studied using the state-of-the-art characterization techniques. SPS was found to carry a higher load of -SO3H functional groups (1.62 mmol H+ per g) compared to SGA (1.23 mmol H+ per g), contributing to its slightly higher efficiency in the regioselective ring-opening of 2-(phenoxymethyl)oxirane with indole. Under mild and solvent-free conditions, SPS catalyzed the reaction of various indoles and oxiranes (9 examples) with acceptable yields (55–99%). The catalyst’s efficiency was further validated in synthesizing various bis(indolyl)methanes (8 examples, 88–99% yield). Recyclability tests confirmed the stability of SPS over multiple cycles, maintaining significant catalytic activity. This study highlights the potential of SPS as a sustainable and efficient catalyst, offering a greener alternative to conventional methods and promoting the valorization of plastic waste in organic synthesis.